Psychometric Evaluation of the Parent Effort Scale - Bevans, Katherine B.; Hallock, Taye M.; Piller, Aimee; Pfeiffer, Beth (Frontiers in Rehabilitation Sciences, 2022)
Objective The Parent Effort Scale (PES) is a parent report questionnaire designed to quantify the level of effort required of caregivers to assist their children in developmentally appropriate home- and community-based activities. This manuscript describes the psychometric evaluation of the PES. Method Data collected from 304 parents of children ages 2–7 years (167 parents of a children with autism spectrum disorder and 137 parents of neurotypical children) were factor analyzed, calibrated using item response theory, and evaluated for construct validity. Results The final PES scales are reliable and valid measures of the level of parental effort required to assist children in dressing, personal hygiene, sleep, socialization at home, participation in community events, and access to healthcare. A total score reflects overall parental effort. Conclusion The PES can be used to plan and evaluate the effectiveness of interventions that aim to help parents enhance children's participation opportunities and thus, support their cognitive and social development.